Interaction of a finite train of short pulses with an atomic ladder system - Jang, H. U.; Lomsadze, B.; Trachy, M. L.; Veshapidze, G.; Fehrenbach, C. W.; DePaola, B. D. (My University, 2010)
When a train of optical pulses interacts with a medium, the time between pulses and the pulse-to-pulse phase jump have a profound effect on the outcome of the interaction. For a near-infinite train of regularly separated pulses having a constant pulse-to-pulse phase jump, as in the output of a frequency comb laser interacting with a ladder system, excitation of that system has been previously calculated and compared with experiment. In that case, the number of pulses in the train is very large, and the energy per pulse is very small. In the present work, the other extreme is experimentally examined: A small number of regularly spaced optical pulses are made to interact with a three-level ladder system in atomic rubidium. The pulses have been amplified, possibly placing the interactions into a nonperturbative regime. The experimental results are compared to a simple intuitive model and found to be in good general agreement. However, some aspects of the experimental results seem to be at odds with the simple model.